Clinical study of electroacupuncture on the recovery of gastrointestinal dysfunction after laparoscopic surgery for gastrointestinal cancer - study protocol for a randomized controlled trial - Shuet Ling Chung; Wen Li; Qiuyue Wang; Xiaofeng Qiu; Yuncheng Tang; Sheng Hu; Huangan Wu; Zhu Jin (BMC, 2024)
Abstract Background Gastrointestinal dysfunction is one of the common complaints for patient post-surgery. Acupuncture has been employed to improve gastrointestinal function and sleeping quality and has confirmed clinical efficacy for emotional problems. This study aims to evaluate the clinical effect of electroacupuncture for postoperative rapid recovery. Methods This study design is a two-arm, parallel, double-blinded randomized controlled trial. 104 subjects, aged from 40 to 89 years old, diagnosed with gastrointestinal cancer undergoing laparoscopic surgery, will be divided into Interventional Group and Control Group. Patients of both groups receive perioperative care under the guidance of ERAS guidance. The Interventional Group receives electroacupuncture treatment starting from the first day post-surgery for a consecutive 5 days, whereas the Control Group receives placebo electroacupuncture treatment. The primary outcome will be the first flatus time whereas the secondary outcomes will be the first sign of borborygmus, recovery of defecation, laboratory tests and questionnaires including Self-rating anxiety scale, Ford Insomnia Response to Stress Test, TCM rating scale of Gastrointestinal symptoms and Gastrointestinal Symptoms Rating Scales. Discussion This study aims to provide timely intervention for post-laparoscopic patients with gastrointestinal tumour using the ERAS concept combined with electroacupuncture, observe the efficacy of this therapy in treating PGID, and contribute reliable scientific evidence for postoperative rapid recovery. Trial registration Chictr.org.cn Identifier: ChiCTR2300078710. Registered on 15th December 2023.